2008
DOI: 10.1103/physrevb.77.075410
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size and surface structure on adsorption of O and OH on platinum nanoparticles: A first-principles study

Abstract: Using first-principles density functional theory, we study the effect of particle size and surface structure on the chemisorption energy of OH and O on nanoparticles of Pt. We find that the chemisorption energies of O and OH are strongly affected by the size and structure of the Pt particle varying by up to 1.0 eV at different adsorption sites and particle sizes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
199
1
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(226 citation statements)
references
References 53 publications
25
199
1
1
Order By: Relevance
“…The effects of coordination environment on surface energies appear to be much stronger than any effects of curvature enforced by size alone, 24,35 suggesting that the effects of size on bulk oxidation are much more modest than previously claimed. 36 The conclusion that the strong effects of cluster size on NO oxidation turnovers do not reflect preferential bulk oxidation of small clusters is consistent with NO oxidation turnover rates measured after thermal treatments intended to reduce or oxidize Pt clusters (Figure 6).…”
mentioning
confidence: 72%
See 1 more Smart Citation
“…The effects of coordination environment on surface energies appear to be much stronger than any effects of curvature enforced by size alone, 24,35 suggesting that the effects of size on bulk oxidation are much more modest than previously claimed. 36 The conclusion that the strong effects of cluster size on NO oxidation turnovers do not reflect preferential bulk oxidation of small clusters is consistent with NO oxidation turnover rates measured after thermal treatments intended to reduce or oxidize Pt clusters (Figure 6).…”
mentioning
confidence: 72%
“…In contrast, CO oxidation turnover rates, also limited by molecular adsorption of O 2 , but on CO*-covered surfaces, are independent of Pt or Pd cluster size (1.5-10 nm). 28,29 Apparently, the size effects on binding energy are less pronounced for CO, which prefers atop sites, 30 than for O*, which prefers multicoordinate sites 24 whose binding properties more strongly depend on surface structure.…”
Section: Experimental Methods 21 Catalyst Synthesis and Characterizmentioning
confidence: 99%
“…This effect is not as pronounced as in our previous study [21]; however, the same conclusions could be drawn to explain the shift in the Pt-oxide peak. Isolated nanoparticles have a higher adsorption energy for oxygenated species compared to Pt agglomerates and extended surfaces; hence, the Pt-O peaks will occur at lower potentials for samples containing Pt nanoparticles [8,13,21,28]. It has been shown that CO stripping could be used to investigate the change of morphology of a Pt surface, i.e.…”
Section: Electrochemically Active Surfacementioning
confidence: 99%
“…Furthermore it is reported that the edge sites, which increase in fraction of total surface sites with decreasing particle size, have lower specific activity due to very strong oxygen binding energies [19][20][21][22]. Even with the same alloy metal combinations, the particle size effects are difficult to delineate as the heat treatment used to increase particle size results in a varied degree of alloying, and, thus, different surface activity [23,24].…”
Section: Introductionmentioning
confidence: 99%